Pengaruh Gaya Kepemimpinan Transformasional Dan Budaya Organisasi Terhadap Kinerja Karyawan Melalui Motivasi Sebagai Variabel Intervening Pada Pt. Taspen - Reza Heriansyah; Ipan Hilmawan (Sains: Jurnal Manajemen dan Bisnis, 2017)
This study aims to analyze the effect of transformasional leadership and organization culture on employee performance with motivation as an intervening variable on employees of PT. TASPEN (Persero) Serang.In this study, there are four variables, namely Transformasional Leadership (X1), Organization Culture (X2), Employee Performance (Y), and Motivation (Z). The study involved 54 samples of employees of PT. TASPEN (Persero) Serang.To obtain accurate results in this study using interviews, observations, and questionnaires. This research uses descriptive method, data analysis, instrument test, multiple regression analysis, t test, intervening variable path analysis and sobel test with SPSS v22 calculation.The result of this research showed that : (1) Transformasional Leadership is negative and not significant impact on the Motivation, (2) Organization Culture is negative and not significant impact on the Motivation, (3) Transformasional Leadership positive and significant impact on the Employee Performance, (4) Organization Culture positive and not significant impact on the Employee Performance, (5) Motivation positive and significant impact on the Employee Performance.